2012
DOI: 10.1016/j.ijrobp.2012.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Copper-64-diacetyl-bis(N(4)-methylthiosemicarbazone) Pharmacokinetics in FaDu Xenograft Tumors and Correlation With Microscopic Markers of Hypoxia

Abstract: Purpose The behavior of 64Cu-ATSM in hypoxic tumors was examined through a combination of in vivo dynamic PET imaging, and ex vivo autoradiographic and histological evaluation using a xenograft model of H&N squamous cell carcinoma. Methods and Materials 64Cu-ATSM was administered during dynamic PET imaging, and temporal changes in 64Cu-ATSM distribution within tumors were evaluated for at least 1 h and up to 18 h. Animals were sacrificed at either 1 h (cohort A) or after 18 h (cohort B) post-injection of rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 16 publications
(23 reference statements)
0
44
1
Order By: Relevance
“…Also, different relationships between pO 2 and the spatial distribution of 64 CuCl 2 and 64 Cu-ATSM were found. The level of tumor uptake and tumor-to-background ratios of both 64 Cu-ATSM and 64 CuCl 2 found in this study seems to be lower than has previously been reported (14,20,33). However, during the 1-h dynamic scans, the tumor-to-muscle ratios of both 64 Cu-ATSM and 64 CuCl 2 continued to increase and did not reach a plateau.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Also, different relationships between pO 2 and the spatial distribution of 64 CuCl 2 and 64 Cu-ATSM were found. The level of tumor uptake and tumor-to-background ratios of both 64 Cu-ATSM and 64 CuCl 2 found in this study seems to be lower than has previously been reported (14,20,33). However, during the 1-h dynamic scans, the tumor-to-muscle ratios of both 64 Cu-ATSM and 64 CuCl 2 continued to increase and did not reach a plateau.…”
Section: Discussioncontrasting
confidence: 74%
“…A previous study on nude rats with FaDu tumors found no correlation between hypoxia marker, pimonidazole, and intratumoral spatial distribution of 64 Cu-ATSM 1 and 18 h after injection (20). In contrast, another study using the same tumor model found that there was no temporal change in the intratumoral distribution of 64 Cu-ATSM early (2 h) or late (16 h) after injection and that pO 2 probe measurements from different tumor sections corroborated well with PET images (21).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The short-lived radionuclides can be used for sequential measurements, whereas radionuclides with longer half lives do Table 2 for full names. Lewis et al [133] , Yuan et al [134] , Kersemans et al [135] , Matsumoto et al [136] Ballegeer et al [137] , Bowen et al [138] , Lewis et al [133] , Myerson et al [139] , O'Donoghue et al [72] Ballegeer et al [137] , Hansen et al [140] , Matsumoto et al [136] , McCall et al [66] , O'Donoghue et al [72] , Oh et al [74] , Yuan et al [134] Grigsby et al [141] , Tateishi et al [142] , Valtorta et al [143] , Weeks et al [144] Dence et al [145] , Kersemans et al [135] , Lewis et al [146] , Matsumoto et al [136] , O'Donoghue et al [72] Dehdashti et al [86] , Lohith et al [67] , Wong et al [80] , Zhang et al [81] Chao et al [147] , Dehdashti et al [148] , Dehdashti et al [149] , Dietz et al [150] , Grassi et al [151] , Grigsby et al [141] , Kositwattanarerk et al [152] , Laforest et al [153] , Lewis et al [154] , Minagawa et al [155] , Nyflot et al [156] [ Mahy et al [158] , Mahy et al …”
Section: F]fetnim and [mentioning
confidence: 99%
“…In oncology, [Cu]ATSM has been evaluated both preclinically and clinically. This tracer shows favorable kinetics with rapid uptake in hypoxic tissue and fast clearance from normoxic tissues, enabling imaging within 30 min after injection [66,67] . However, the exact uptake mechanism of [Cu]ATSM is still under debate [63,68,69] and several preclinical studies have shown that [Cu]ATSM uptake depends on tumor type and other characteristics than hypoxia alone [70][71][72][73][74][75][76] .…”
Section: F]fmisomentioning
confidence: 99%